1999
DOI: 10.3109/08820139909022722
|View full text |Cite
|
Sign up to set email alerts
|

Coincidence of hereditary angioedema (HAE) with Crohn's Disease

Abstract: A patient with two diseases, based presumably on different immunopathological mechanisms, hereditary angioedema (HAE) and Crohn's disease, was followed for 8 years. For more than three years of this observation period, detailed laboratory data were also available and could be analyzed. Both diseases had severe courses requiring chronic treatment with danazol and sulfasalazine, respectively. During exacerbation of Crohn's disease, the levels of C4 was found to be significantly lower than during the periods free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
2

Year Published

2004
2004
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 20 publications
0
13
0
2
Order By: Relevance
“…Plusieurs cas d'OAH associés à des maladies autoimmunes ont été rapportés, en particulier la polyarthrite rhumatoïde [6], la maladie de Crohn [7] ou le lupus érythé-mateux systémique (LES) [8]. Dans ce dernier cas, les taux bas de C4 et C2 prédisposeraient au développement de la maladie.…”
Section: Discussionunclassified
“…Plusieurs cas d'OAH associés à des maladies autoimmunes ont été rapportés, en particulier la polyarthrite rhumatoïde [6], la maladie de Crohn [7] ou le lupus érythé-mateux systémique (LES) [8]. Dans ce dernier cas, les taux bas de C4 et C2 prédisposeraient au développement de la maladie.…”
Section: Discussionunclassified
“…A thorough literature review has revealed very few case reports of urticaria or angioedema associated with IBDs. These include cases of Hereditary angioedema associated with Crohn's disease [12,13] , angioedema of the small intestine masquerading as Crohn's disease [14,15] , and a single case of chronic urticaria without angioedema in a patient who was subsequently diagnosed with Crohn' s disease [16] . There has also been a case report of chronic urticaria and ulcerative colitis [17] .…”
Section: Discussionmentioning
confidence: 99%
“…In the cases in question, however, the diagnosis of CD is better established, and symptoms responded to sulfasalazine. Furthermore, in one patient who was closely investigated over 8 years,107 exacerbations of bowel inflammation never coincided with those of cutaneous angioedema, and were notable for transiently reduced serum C4 levels.…”
Section: Complement Dysfunctionmentioning
confidence: 95%
“…A series of patients have also been reported in whom CD‐like small bowel enteritis arose in the context of C1 esterase deficiency, usually associated with hereditary angioedema 106–108. If the bowel wall becomes edematous, patients may present with colicky abdominal pain, mimicking the symptoms and macroscopic (but not microscopic) appearances of IBD.…”
Section: Complement Dysfunctionmentioning
confidence: 99%